(untitled) (Web of Teachers: Inderscience Research, 2025)
This article covers the psychological foundations of the formation of leadership qualities in employees of internal affairs bodies. The importance of such qualities as leadership skills, responsibility, initiative, ability to manage a team is analyzed in the personal and professional development of employees. Psychological theories, leadership styles and ways to introduce them into practice are considered.